2016
DOI: 10.1073/pnas.1607231113
|View full text |Cite
|
Sign up to set email alerts
|

Na + coordination at the Na2 site of the Na + /I symporter

Abstract: The sodium/iodide symporter (NIS) mediates active I− transport in the thyroid—the first step in thyroid hormone biosynthesis—with a 2 Na+: 1 I− stoichiometry. The two Na+ binding sites (Na1 and Na2) and the I− binding site interact allosterically: when Na+ binds to a Na+ site, the affinity of NIS for the other Na+ and for I− increases significantly. In all Na+-dependent transporters with the same fold as NIS, the side chains of two residues, S353 and T354 (NIS numbering), were identified as the Na+ ligands at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 92 publications
1
9
0
Order By: Relevance
“…The sodium binding pocket comprises the homologous residues S64 and S67 in TM2; T188, D189 and Q192 in TM6; S347, T349, S351, T352, S354 and S355 in TM9; and, Q261 in TM7 ( Figure 2 B). Notably, while this work was being developed, Ferrandino et al reported computational and biochemical data supporting the role of residues S66, D191, Q194, and Q263 in coordinating sodium in hNIS at the Na2 site, 62 providing independent confirmation of our findings. We propose, therefore, that at least one sodium ion involved in hNIS and hSMCT1 substrate transport is coordinated by a binding pocket conserved between both proteins.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The sodium binding pocket comprises the homologous residues S64 and S67 in TM2; T188, D189 and Q192 in TM6; S347, T349, S351, T352, S354 and S355 in TM9; and, Q261 in TM7 ( Figure 2 B). Notably, while this work was being developed, Ferrandino et al reported computational and biochemical data supporting the role of residues S66, D191, Q194, and Q263 in coordinating sodium in hNIS at the Na2 site, 62 providing independent confirmation of our findings. We propose, therefore, that at least one sodium ion involved in hNIS and hSMCT1 substrate transport is coordinated by a binding pocket conserved between both proteins.…”
Section: Resultssupporting
confidence: 83%
“…The participation of residues S66, D191, Q194, and Q263 in hNIS-mediated iodide uptake has been recently demonstrated by experiments. 62 The hNIS and hSMCT1 models are oriented with the extracellular side toward the top of the page. (C) Sequence logo illustrating conservation of the residues (indicated with arrows) predicted to coordinate the Na + ion.…”
Section: Resultsmentioning
confidence: 99%
“…Mouse Tlr4 promoter constructs þ52/þ223, À104/þ223, À336/þ223, and À608/þ223 were as reported previously (24). Disruption of the distal Ets-binding site in the mouse Tlr4 promoter was performed by PCR with the oligonucleotide 5 0 -TGGGTTTT-AATCTCTAGCATTGTGAGAAAATATGTAGTTCTAGTCTGAAAC-ATCCA carrying the desire mutation (underlined) using KOD Hot Start DNA polymerase (EMD Millipore) as described previously (25). The artificial ETS reporter 3x Ets d -Luc contains the luciferase gene under the control of a promoter containing three copies in tandem of the flanking region of the distal Ets-binding site (AAAATATGTTCCTCTAGTCTGA) of mouse Tlr4 promoter upstream the adenovirus E1B core promoter.…”
Section: Plasmidsmentioning
confidence: 99%
“…The mechanism by which NIS transports its various monovalent anionic substrates remains poorly understood. NIS does not transport every monovalent anion and it is still unclear what differentiates a substrate from an inhibitor or irrelevant anion [13,[83][84][85][86][87]. Here we compared the anion selectivity and inhibitor sensitivity of NIS proteins from diverse animal species and found, unexpectedly, that they differ not only in their ability to transport the NIS substrates 99m , but also in their susceptibilities to inhibition of iodide transport by a wide range of monovalent anions.…”
Section: Discussionmentioning
confidence: 84%
“…Mapping of the residues in direct contact with the transported ions revealed no significant differences in the sampled models in terms of residue identity and side chain positions between the three species of NIS protein (Fig 8B-8E). Several of these residues have been previously reported as crucial for NIS activity [53,85,86]. Within the hNIS, wNIS, and zNIS subset, the differing residues in the binding areas are at positions 64, 188, and 195, where only the substitution at position 64 (S64C in wNIS and S64A in zNIS) leads to change in the chemical properties of the side chain.…”
Section: Discussionmentioning
confidence: 96%